Filling key gaps in population and community ecology. Issue 9 (1st April 2007) - Agrawal, Anurag A.; Ackerly, David D.; Adler, Fred; Arnold, A Elizabeth; Cáceres, Carla; Doak, Daniel F.; Post, Eric; Hudson, Peter J.; Maron, John; Mooney, Kailen A.; Power, Mary; Schemske, Doug; et al.
Abstract : We propose research to fill key gaps in the areas of population and community ecology, based on a National Science Foundation workshop identifying funding priorities for the next 5–10 years. Our vision for the near future of ecology focuses on three core areas: predicting the strength and context‐dependence of species interactions across multiple scales; identifying the importance of feedbacks from individual interactions to ecosystem dynamics; and linking pattern with process to understand species coexistence. We outline a combination of theory development and explicit, realistic tests of hypotheses needed to advance population and community ecology.